Clinical outcomes of pregnancy in patients with pulmonary hypertension: A single center observational study - Jianrong Pan; Qingsong Wu; Shixin Chen; Huilan Wang; Qimin Wang (Journal of Cardiothoracic Surgery)
Abstract Background Pulmonary hypertension (PH) is associated with right ventricular failure in pregnant women and increases maternal morbidity and mortality during parturition and postpartum periods. According to current guidelines, pregnancy is contraindicated in women with PH. However, in recent decades, favorable outcomes have been observed in cases where the disease is well controlled. However, several questions remain unanswered regarding this issue. Objective This study aimed to investigate the medium-term outcomes of pregnancy in women with PH and to identify predictors for poor pregnancy outcomes in this population. Methods A retrospective review of the medical records at our hospital was conducted to identify pregnant women with PH between July 2017 and December 2021. We collected data on maternal age, gravidity, parity, PH category, New York Heart Association Function class, N-terminal-pro Brain natriuretic peptide (NT-ProBNP) levels, mode of delivery, type of anesthesia, use of advanced therapy, and fetal outcomes. Based on the severity of PH, patients were categorized into three groups: group A systolic pulmonary arterial pressure (SPAP) 40–50 mmHg, group B 50–70 mmHg, and group C SPAP ≥ 70 mmHg. Results The study included 78 individuals in group A, 22 in group B, and 18 in group C. Of the 118 individuals, 80 were classified as having pulmonary arterial hypertension (PAH), including congenital heart disease-associated PAH, idiopathic PAH, and other PAH subtypes, while 38 were classified as having PH associated with left heart disease (PH-LHD). The mortality rate was higher in the PAH category (6.3%, 5/80) than in the PH-LHD category (2.6%, 1/38). The NT-proBNP value was highest in group C (1723.5 ± 738.0pg/ml), compared with group B (196.6 ± 79.6 pg/ml) and group A (128.7 ± 54.3 pg/ml). Overall maternal mortality was 5.1% (6/118), with significantly higher mortality rates observed in group C (27.8%, 5/18) compared to group B (4.6%, 1/22), and no deaths in group A. Compared to groups A and B, gestational duration was shorter (median 26 weeks), and abortion rates were higher (38.9%, 7/18) in group C. Cesarean section rates were high across all three groups. The overall maternal mortality rate was 5.1% (6/118). Of them, five individuals were in group C, only one woman had moderate PH with perinatal cardiomyopathy and a lower LVEF of 15%. There was no maternal mortality in Group A with mild PH. All maternal deaths occurred postpartum. Excluding 17 cases of miscarriage (gestation less than 28 weeks), the overall offspring mortality rate was 4.0% (4/101), with one fetal mortality in group B, three fetal deaths in group C, and no fetal mortality observed in group A. Conclusion Severe PH and high NT-proBNP levels are strongly correlated with increased maternal mortality rates in pregnant women. Conception should be contraindicated in cases of severe PAH with elevated NT-proBNP levels. In situations where unplanned pregnancy occurs in severe PAH patients with decompensated heart function, early pregnancy termination and multidisciplinary management are crucial to ensure maternal safety. However, pregnancy should be considered individually in women with moderate and mild PH and preserved right heart function.